Evaluating the effectiveness of coaching methods on competence and performance in Early Childhood Islamic Education (PIAUD) students - Selian, Nurhaida; Muzaimah, Muzaimah; Sari, Nelta (STAI Auliaurrasyidin Tembilahan, 2025)
This study evaluates the effectiveness of the coaching method in enhancing the competencies and performance of students in the Early Childhood Islamic Education (PIAUD) Study Program at STAIN Bengkalis. Coaching is a structured, personalized approach aimed at developing students' potential in both academic and non-academic aspects. A qualitative descriptive method was used, collecting data through interviews, observations, and document studies to explore students' experiences with the coaching process. The findings indicate that coaching positively impacts students' leadership, time management, problem-solving skills, as well as academic performance, communication, and self-confidence. Students reported greater clarity in setting goals and increased motivation. Key success factors include active student engagement, guidance from academic supervisors, and a supportive learning environment. However, challenges such as time constraints and initial confusion about the coaching process were identified. This study concludes that coaching can significantly enhance students' competencies and performance, with proper implementation in a supportive environment. It recommends the broader adoption of coaching in the PIAUD program, tailored to local contexts and needs.